Analysis of hourly generation patterns at large coal-fired units and implications of transitioning from baseload to load-following electricity supplier - Robert Kennedy Smith (Journal of Modern Power Systems and Clean Energy, 2019)
Several factors have led to the decline of electricity generation from coal over the past decade, and projections forecast high rates of growth for wind and solar technologies in coming years. This analysis uses hourly generation data from large coal-fired power stations to determine how operations have been modified in recent years and describes the implications of these changes for plant equipment and unit reliability. The data shows increasing variability in intraday generation output that affects nearly all of the units in the sample, but the magnitude of increase varies widely among plants. Outage patterns were examined as was the relationship between renewable energy growth in a region and the changes in coal plant operations. Aggregate direct and indirect costs associated with running coal plants as load-following units have not yet been quantified in large-scale studies on a sector-wide basis, largely due to differences in how specific equipment responds to output fluctuations. Due to findings from the hourly generation data analysis and the high degree of potential impact on coal plant equipment, the study suggests the development of a new modeling tool that will represent the costs of running coal-fired power plants at lower capacity factors.